Calibration and Storage of DNA Competitors Used for Contamination-Protected Competitive PCR - Thomas Köhler; Anne-Katrin Rost; Harald Remke (BioTechniques)
DNA fragments used as standards in competitive PCR were precisely calibrated using HPLC and commercially available DNA molecular mass markers. The accuracy of calibration was reflected by data that differed by only 2% from the mean when two independently purified and calibrated competitor preparations were compared. Highly dilute competitor solutions were stable at -20°C for up to 1 year in the presence of carrier HindIII-digested γDNA, but progressive loss of competitor DNA with increasing storage time was observed when carrier DNA was omitted from the solution. Applying 0.2 U uracil-DNA glycosylase (UDG) per assay of remaining temperaturestable activity did not effect the ratios of synthesized products. This study describes quality management in PCR quantitation that is useful for the measurement of multidrug resistance-associated protein (MRP) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene transcripts.